Improved Shape-Finding Method and Parametric Study for Designing Asymmetric Suspension Bridges in Mountainous Terrain - Chenchen Jiang; Yangxun Ou; Weiyu Tang; Shengjun Hou; Rui Luo; Yuhao Jin; Bin Sun (Advances in Civil Engineering)
The suspension bridges in mountainous areas are commonly designed with asymmetrical overall layouts to match the terrain and construction under limited space. However, the effects and influences of the asymmetry parameters on the bridge performance have yet to be thoroughly investigated. To address this gap, based on a real-world suspension bridge with a main span length of 700 m, this paper first presents an improved shape-finding method that can fully consider the components of hanger forces in each construction step. In the iterative process, the shape of the cable is determined based on the equilibrium equations, and the hanger forces are calculated through the nonlinear finite element analysis. After deciding the bridge’s initial state, the asymmetry parameters’ effects are carefully investigated through finite element analysis under the static and seismic conditions. Results show that the side-to-span ratio of the main cable and the tower’s stiffness can affect the horizontally constrained stiffness, resulting in distinct bridge behavior. Moreover, reasonably designing the dampers between the tower and the girder can be beneficial in minimizing the longitudinal displacement and controlling the tower’s moment under the seismic situations.